Digital Business Models in Network Management - Adam Jabłońsk (MDPI, 2023)
The digital economy creates new conditions for creating entrepreneurial solutions. Technology determines the emergence of innovative business models, the existence of which would not be possible without the potential of such technologies. The unlimited ingenuity of contemporary entrepreneurs is currently focused on the search for innovative solutions in the sphere of using the opportunities offered by digital technology. It should be noted that the development of new paradigms in the science of management and economics results from transformations in the global economy, where ideas and concepts arise in various places, often thanks to global access to information and knowledge through technological, Internet-based platforms. This is the most crucial assumption of this Special Issue.
Keywords: 650